Heritage and accessible tourism in the Côa region: A review of ideas and concepts - Silva, Maria de Fátima (2020)
The aim of this paper is to develop a holistic conceptual framework to support the development of effective management tools to preserve and explore the potential of a Portuguese low-density region – the Côa River Valley. The Côa River Valley was classified by UNESCO as a World Heritage Site in 1998, recognizing the importance of heritage and natural values, namely the presence of a remarkable open-air ensemble of Palaeolithic art. The significance of this heritage – cultural and natural - justifies an effort of convergence of interests and actions, in order to guarantee a sustained enhancement and integrated management of the diverse patrimonies and the sustainable development of local communities. The region´s development strategy based on the development of tourism activities and products must consider this heritage in the pursuit of accessibility and sustainability. Considering that natural and cultural resources are the main attractions of this territory and the basis of its competitive advantage and endogenous growth, it is essential to take into account how these resources are incorporated into qualified tourism products. Moreover, providing accessibility (in a broad sense, including accessibility of information, social, intellectual and emotional components) to heritage sites is considered a way to promote the regions’ sustainable management. Consequently, there is a need to research how to promote the conditions of universal accessibility, as well as the improvement and creation of new products and services, their diffusion, the increase of cultural offer and the internationalization of the history and identity of this territory, promoting accessible and sustainable tourism. The influence of climate change on cultural and natural heritage, and more specifically on water resources, must also be considered in this framework. Therefore, in order to support the development of effective management tools to preserve and explore the potential the region, the paper presents a literature review, based on an interdisciplinary and multidisciplinary perspective and encompassing the main topics related to the challenges and opportunities of this territory: accessibility and accessible tourism; tourist profile in low density regions; sustainable trends in low density regions; climate change and its impacts on natural and cultural heritage; routes and networks.